Innovative and Strategic Aspects of Intellectual Property Management in State-Owned Enterprises of Georgia - George Chiladze (European Scientific Journal, ESJ, 2020)
Innovative, strategic management of IP is one of the currently urgent problems of the knowledge economy in Georgia. However, at this stage, many state-owned enterprises, organizations as well as enterprises where the state is partial shareholder, have not yet properly assessed the role of IP, as well as of other intangible assets, in creating sustainable competitive advantages, which are provided by the corporate governance standards as well as by the Guiding Principles (Guidelines) developed by the Organization for Economic Co-operation and Development (OECD), recommendations included in the World Bank’s report on corporate governance of state enterprises and the recommendations and best practices related to the management of state-owned enterprises in EU member states. The IP Management Strategy in State-Owned Enterprises simultaneously covers diverse areas of financial, technological, and marketing activities and is also destined to ensure the effective implementation and protection of IP rights. Non-consideration of the IP’s role in the technological development will lead in the near future to decreased investments in innovations, losses in budget accruals and the loss of the promising export trade directions. The IP Management Strategy should mainly include such issues as: increasing the value of intangible assets and creating unique competitive advantages; ensuring technological leadership; providing of returns on investments in innovation; protection of IP rights on the IP objects; lobbying and promotion of trademarks, etc